2018
DOI: 10.1634/theoncologist.2018-0056
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Common Clinical Characteristics and Postoperative Morbidity and Overall Survival in Patients with Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is one of the most feared cancer diagnoses because of its limited survival and treatment. This study revealed significant associations of noncancerous factors on the morbidity and mortality of GBM. The complexity of medical comorbidities, as well as short-term postoperative levels and fluctuations of blood pressure and blood glucose, was associated with postoperative complications, but not overall survival. However, long-term levels of these common clinical parameters were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Limitations of this study include its retrospective nature and power. The sample size is comparable to other single-institution studies, although there was a limited sample size for subgroups for some comorbidities 5,19 . This sample has a higher proportion of nonwhite patients compared to other studies on glioblastoma patients in the literature 2 .…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Limitations of this study include its retrospective nature and power. The sample size is comparable to other single-institution studies, although there was a limited sample size for subgroups for some comorbidities 5,19 . This sample has a higher proportion of nonwhite patients compared to other studies on glioblastoma patients in the literature 2 .…”
Section: Discussionsupporting
confidence: 52%
“…Prior studies evaluating comorbidities and long-term survival in patients with GBM have focused on a limited number of comorbid conditions, primarily diabetes mellitus 19,37 . Additionally, the usual risk of mortality associated with hypertension, diabetes, stroke, and heart disease may be overcome by the drastically higher rate of mortality of patients within our sample population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Liu et al found that lower systolic blood pressure, lower albumin, and higher blood glucose were associated with worse survival. 19 The driving factor for not only elderly patients but all patients with GBM – and likely those undergoing any type of surgery – is how systemically well these patients are and how well-controlled their comorbidities are perioperative. Elderly patients with multiple well-controlled comorbidities should still be offered surgical and adjuvant treatment for GBM.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative serum level of albumin was associated with OS in GBM patients in univariate analysis, but it was not a predictor in multivariate analysis. Previous studies investigating the association between preoperative serum albumin concentration and prognosis of GBM reported that low serum albumin concentration was an independent poor prognostic factor [ 6 , 29 , 30 ]. Lymphocytes, which are the other component of the PNI, play a key role in cell-mediated immunity.…”
Section: Discussionmentioning
confidence: 99%